2017
DOI: 10.17159/2413-3051/2016/v26i4a2092
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the performance of an improved solar-biomass hybrid dryer

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Madhlopa and Ngwalo (2007) developed an indirect type natural convection solar dryer integrated with thermal storage and biomass-backup heater for drying pineapple. Okoroigwe et al (2015) re-designed a solar dryer with frontal pass solar collector integrated with biomass back-up heater by incorporating a back pass solar collector instead of frontal pass solar collector. Barki et al (2012) presented performance evaluation of an efficient solar dryer with a backup incinerator for grated Cassava under Makurdi humid climate.…”
Section: Introductionmentioning
confidence: 99%
“…Madhlopa and Ngwalo (2007) developed an indirect type natural convection solar dryer integrated with thermal storage and biomass-backup heater for drying pineapple. Okoroigwe et al (2015) re-designed a solar dryer with frontal pass solar collector integrated with biomass back-up heater by incorporating a back pass solar collector instead of frontal pass solar collector. Barki et al (2012) presented performance evaluation of an efficient solar dryer with a backup incinerator for grated Cassava under Makurdi humid climate.…”
Section: Introductionmentioning
confidence: 99%
“…Operating with the drying air temperature of 49.8(±2.2)°C and relative humidity of 22(±4)%, and loaded with 100 kg wet fish Bleberan measured about 13.41 (±0.25) cm long, this dryer reduced the moisture content of fish from 81.04% to 20% in 13.4 hours, in contrast working with the drying air temperature ranged from 32. The design of the solar-biomass hybrid dryer introduced here was also unique compared to those reported by other researchers [16], [21], [17], [18]. The uniqueness of this dryer relied mainly on the shape of the structure as depicted in Figure 1, the design of the heat exchanger as described in detail above, and free from electricity dependence which makes it possible for application in remote areas.…”
Section: Resultsmentioning
confidence: 87%
“…To solve this problem, the hybrid solar dryers have been developed. These dryers operate with solar energy and other energies, such as electric energy [13], [14], [15]) and biomass [16], [17], [18], [19], [20] as energy substitution or a combination. The substitution energy is usually supplied from an electric heater or a heat exchanger that transfers heat from combustion stove.…”
Section: Introductionmentioning
confidence: 99%
“…The study also showed that, solar drying of vegetables led to retaining of more nutrients and is relatively hygienic with reduced microbial. Okoroigwe et al (2015) in research study on comparative evaluation of the performance of an improved solar-biomass hybrid dryer, it was found that, a redesigned biomass solar dryer with a back pass solar collector and heat exchanger showed a significant improvement in agricultural drying. The efficiency of the solar dryer based on solar, biomass and a combined solar biomass showed a significant increase in the drying of fresh okra, fresh groundnut and fresh cassava chips when a test was carried out.…”
Section: Solar Drying Research In Nigeriamentioning
confidence: 99%